Fidelización De Clientes En Tiendas Industriales Asociadas (TIA.SA - Paredes Morante, Cinthia Estefanía (2017)
Asociados Industriales Asociadas (TIA) is a company that was founded on November 29, 1960, in the city of Guayaquil, as a chain of stores offering home and personal consumption products, specializing in innovative offers, seasons or events, through a wide national coverage, focusing its strategies towards the population with low socio-economic level expanding its range of location in areas not covered by the competition. . Currently it has 182 premises distributed in 88 cities and 23 provinces. One of these branches is located in Babahoyo (branch 133) which is where the present case study will be developed, which begins its work on January 12, 2005, located in av. Bolívar No. 423 between Av. 5 de Junio ​​and Av. García Moreno